Philosophical, ethical, legal and politicalfoundations for the study of the interrelationshipbetween human rights and democracy - Guadarrama-González, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The approach to the conflictive and polysemic meanings of the concepts of human rights and democracy plays a significant role in the benchmarks, perspectives and aims of the researcher in question. Therefore, a true and accurate understanding of the functions of philosophy to facilitate analysis of human rights and democracy, allows pausing in the assessment of the significance of ideological and legal component in the study of the interaction between them. If the philosophies renounce the concrete utopian intention to intervene actively in the improvement of human behavior, such as the study of human rights in their possible link with democracy, they stop being philosophies, such as when they are thoughtlessly subordinated to political ideological or legal positions rather than promote them rationally.